The relation between clothing retail image and the loyalty of the generation Y’s consumers - De Toni, Deonir; Dal Ponte, Virginia; Graciola, Ana Paula; Milan, Gabriel Sperandio (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
The generation Y is represented by adolescents and young adults that were born between 1980 and 2000. It is the wallet power generation, with estimated annual spending capacity of 200 billion dollars. In this scenario, the principal aim of this research is to identify the relationship between dimensions of the clothing retail image and the loyalty of the generation Y customers. The proposed framework was based on the literature review of store image and loyalty. The survey was applied to 394 generation Y’s consumers. The results indicated that the store image has an impact on the loyalty dimension. Among the dimensions of the image store, the following ones stood out: services, merchandise mix and store atmosphere.